Pengaruh Budaya Organisasi, Kepuasan Kerja Dan Komitmen Organisasi Terhadap Kinerja Tenaga Paramedis Puskesmas Tapan Kecamatan Basa Ampek Balai Kabupaten Pesisir Selatan - Yulihardi, Yulihardi (Sekolah Tinggi Ilmu Ekonomi Riau, 2016)
This study aims to reveal (1) Influence of Organizational Culture on the Performance of Power Medics, (2) Job Satisfaction on the Performance of Power Medics, (3) Organizational Commitment to Performance Power Medics, (4) the effect of Organizational Culture, Job Satisfaction, and Organizational Commitment in together against Paramedical Personnel performance. The population in this study is a Paramedical Personnel Sub-district Puskesmas Tapan Bases Ampek Hall South Coastal District totaling 40 people. In because the population is relatively little overall sample of the population (census) as many as 40 people. Analysis of the independent and dependent variables made through descriptive analysis and regression as well as for proving the hypothesis used t test and F The conclusion that the hypothesis of partial and simultaneous variable Organizational Culture, Job Satisfaction and Organizational Commitment, on the Performance of Power Paramedical proven / accepted in this study by the regression equation Y = 26.632 + 0.308 X1 + 0.263 X2 + 0,363 X3, with a value of t test each masingnya 2,731 and 2,604 and 2,246 with sig. 0.010, 0.018 and 0.027 less than 0.05. Test F with 7.573 sig. 0.000 <0.05 and is therefore variable X1 (Cultural Organizations), X2 (KepuasanKerja), and X3 (Organizational Commitment) partially and simultaneously significantly affect performance Paramedical Personnel (Y). From the results of this study suggested Organizational Culture, Job Satisfaction and Commitment are relatively good to be maintained and even improved so that performance Paramedical Personnel increasing.